Barriers to contraceptive access and use among youths (15–24 Years) living in informal urban settlements of Kigali, Rwanda: a qualitative study - Emmanuel Okiror Okello; Alexandre Edgard Murinzi; Colyse Nduwimana; Rashidah Nambaziira (Discover Public Health)
Abstract Background Contraceptive use among youths below 19 years in Rwanda is still very low, as low as 3.7%, yet their level of sexual activity is high. By 2020, 42% and 31% of women and men respectively had initiated sex before the age of 20 years. Rwanda’s total population is composed of 67% young people below 25 years. Low contraceptive use among this youth population increases their risk of unintended pregnancies, sexual violence, and sexually transmitted infections. Additionally, 61.3% of Rwanda’s population lives in informal settlements/slums. We conducted a qualitative study to identify the barriers to contraceptive access and use among youths aged 15–24 years, living in informal urban settlements in Kigali. Methodology This was a cross sectional study that employed qualitative methods of data collection. Forty-five participants were conveniently and purposively selected and guided interviews were conducted with them in six focused group discussions and thirteen in-depth interviews. Recorded audios were transcribed and translated from Kinyarwanda to English before a deductive thematic analysis was conducted. Results Barriers faced by the participants were summarized deductively into four themes. (1) Accessibility barriers – including inconveniently located service points, far service points, not knowing where to go with health facilities; (2) Accommodation barriers– perceived or real lack of confidentiality and privacy at service points and among service providers, long waiting time,; (3) Affordability barriers – expensive contraceptives and financial challenges; (4) Availability barriers –unavailability and constant stock out and 5)Acceptability barriers – concerns about contraceptives (myths), fear of side effects, busy/absent service providers, feeling embarrassed/guilty, service provide bias, restrictive laws and parental restriction. Conclusion The youths living in impoverished communities within large cities face a lot of challenges accessing and utilizing reproductive health services. In this study several accessibility, acceptability, accommodation, availability and affordability barriers were identified. The government and other implementing partners can benchmark on these barriers to improve the contraceptive and reproductive health services for youths living in informal urban settlements.